In vitro and in vivo evaluation of a primaquine prodrug without red blood cell membrane destabilization property - Davanco, Marcelo Gomes [UNESP]; Campos, Michel Leandro [UNESP]; Nogueira, Marco Antonio [UNESP]; Campos, Silvio Lopes [UNESP]; Marques, Ricardo Vian [UNESP]; dos Santos, Jean Leandro [UNESP]; Chin, Chung Man [UNESP]; da Fonseca, Luiz Marcos [UNESP]; Peccinini, Rosangela Goncalves [UNESP] (Wiley-Blackwell, 2012)
Primaquine is an important therapeutic resource for malaria treatment and it has wide activity against several pathogens. The haematotoxicity of primaquine is the major problem for its therapeutic application. This effect is aggravated by repeated use at high doses and by the wide fluctuation of plasma levels after administration. The primaquine prodrug (Phe-Ala-PQ) was planned in order to modify the pharmacokinetics and toxicity of primaquine. The in vitro conversion of Phe-Ala-PQ to primaquine, and the primaquine pharmacokinetics were evaluated in four groups of rats: two groups that received a single dose of Phe-Ala-PQ, one by intravenous and the other by gavage route, and two other groups that received primaquine diphosphate, by intravenous and gavage routes. In addition, the erythrocyte osmotic fragility was compared in two groups of rats that received multiple doses of primaquine diphosphate or Phe-Ala-PQ, as a parameter of haematotoxicity. The in vitro conversion of Phe-Ala-PQ to primaquine by plasma enzyme action was observed. The pharmacokinetic profile of primaquine from Phe-Ala-PQ was more favourable due to the lower fluctuation of plasma concentrations. Haematotoxicity was not evidenced in the prodrug administration. The results reinforce the need for further studies with this prodrug, promising an alternative in the therapeutic use of primaquine. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: primaquine; prodrug; pharmacokinetics; preclinical pharmacokinetics; haemolysis